Thematic and linguistic representations of cultural identity in Batak Toba songs (1980–2025) - Pasaribu, Arsen Nahum; Manik, Sondang (Research Journal in Advanced Humanities, 2026)
Although songs of Batak Toba are crucial for the survival of language, transmission of values, and ethnic pride, up to now most of the previous research has only been analyzed from a certain point of view such as the role of gender, speech patterns, or semiotics. This prohibits thematic, cross-time studies from being conducted. To address this void, the current study took a descriptive qualitative approach to examine the lyrics of 100 Batak Toba songs composed between 1980 and 2025. The lyrics were coded, clustered, and interpreted according to Braun and Clarke’s thematic analysis to identify the major cultural themes. The analysis revealed five motifs: love and romance, family and kinship, spirituality and faith, cultural identity and homeland, and counsel, morality, and life’s challenges. Love and romance was the most frequent theme, including happiness, loyalty, tension, and sorrow. Family and kinship featured parental sacrifice, respect and intergenerational relationships. Spirituality and faith were expressed through Christian belief and Batak values, and cultural identity and homeland invoked pride and nostalgia as well as an emotional tie to the land of ancestors even as the people migrates. Counsel and morality redressed determination, good attitude, and intergenerational wisdom. These themes are closely connected to Batak Toba philosophy in general and more specifically to the Dalihan Na Tolu (batak “three-legged furnace”) philosophy in terms of (respect, love, harmony), as well as the ideals of Hasangapon (honor), Hagabeon (future generation), and Hamoraon (wealth). This study reveals Batak Toba songs as living cultural archives where private feelings and collective identity are entwined; Thus, this research signifies Batak Toba songs as a cultural archive. It also suggests a closer interdisciplinary examination of ethnomusicology and cultural studies on the way indigenous philosophies inform creative output.